Analysis of risk factors of acute kidney injury in organ donors - Zheng, Donghua; Zhan, Yaping; Yang, Yanxia; Tai, Qiang; Xu, Guixing (International Journal of Medical Research and Review, 2019)
Background: To investigate the occurrence and risk factors of acute kidney injury (AKI) in organ donors. Methods: Clinical data of 153 donor patients who donated organs in our hospital from January 2016 to July 2018 were collected. Patients were divided into AKI group and non-AKI group according to AKI diagnostic criteria. Clinical indicators of patients in the two groups were compared, and the related risk factors were analyzed by unifactorial and multivariate logistic regression. Results: The incidence of donor patients complicated with AKI was 48.37%. Unifactorial analysis suggested that the SOFA score, positive rate of blood culture, hypothermia incidence and vasoactive drug dose in donor AKI group were larger than those in non-AKI group. Multivariate Logistic regression analysis showed that the dose of booster drugs (P=0.02, OR=3.53) and the positive rate of blood culture (P=0.01, OR=6.64) were independent risk factors for donor patients complicated with AKI. Conclusion: The incidence of acute kidney injury in organ donors is high, with the dose of booster drugs and the positive rate of blood culture as independent risk factors for evaluation basis to assess the incidence rate of donor patients complicated with AKI.